74 HIF2α Downregulation and Clinical Outcomes in Patients with Clear Cell Renal Cell Carcinoma with and without Sarcomatoid Differentiation - Rashad Nawfal; Elio Ibrahim; Karl Semaan; Ali Hajj Ali; Talal El Zarif; Razane El Hajj Chehade; Gunsagar Gulati; Damien Vasseur; Garyoung Gary Lee; Ze Zhang; Gwo Shu Mary Lee; Ji-Heui Seo; et al. (The Oncologist, 2026)
Abstract Background Clear cell renal cell carcinoma (ccRCC) with sarcomatoid differentiation (sRCC) is associated with poor survival. Recent studies have shown downregulation of hypoxia-related pathways in sRCC (Motzer et al., Cancer Cell, 2020; El Zarif, Semaan et al., Cell Reports, 2024). In this study, we sought to compare HIF2α expression levels in ccRCC, with and without sarcomatoid differentiation and investigate clinical outcomes of patients (pts) with sRCC treated with HIF2α inhibitors (HIF2αi). Methods To assess HIF2α gene expression in sRCC, RNA-seq data was collected from 2 clinical trials: JAVELIN Renal 101 (JR101), and IMmotion151 (IM151), as well as publicly available data from The Cancer Genome Atlas (TCGA). Mean HIF2α expression levels were compared between ccRCC with and without SD using Wilcoxon Rank-Sum test. To evaluate the clinical outcomes of pts with sRCC treated with HIF2αi, we also collected clinical data from pts with ccRCC who were treated with Belzutifan between January 2018 and December 2025 at the Dana-Farber Cancer Institute. Progression-free survival (PFS) and overall survival (OS) were analyzed using log-rank test and multivariable Cox regression model accounting for age, IMDC risk group, line of therapy, and type of regimen (HIF2αi; HIF2αi + Vascular endothelial growth factor-targeted therapy (VEGF-TT)). In addition, we performed a similar survival analysis on patients who were also treated with immunotherapy-based regimens from the same cohort. Results RNA-seq data from 2,075 pts with renal cell carcinoma with a clear cell component from TCGA (48 sRCC; 493 ccRCC), JR101 (97 sRCC; 639 ccRCC) and IM151 (110 sRCC; 688 ccRCC) were included. Expression of EPAS1, which encodes for HIF2α, was significantly downregulated in pts with sRCC in TCGA (log(TPM) mean: 6.63 vs 9.95 in ccRCC ; p < 0.001), JR101 (8.71 vs 8.93 in ccRCC ; p = 0.04) and IM151 (8.05 vs 8.69 in ccRCC ; p < 0.001). For the clinical cohort, 140 pts treated with Belzutifan were included with a median follow up of 13 months. In multivariable analysis, sRCC was associated with worse PFS (HRadjusted: 2.04; 95% CI: 1.22–3.42; p = 0.006) and worse OS (HRadjusted: 2.56; 95% CI: 1.35–4.8; p = 0.004) (Figure). In parallel, from the same cohort, 120 patients were also treated with immunotherapy; 16% (19/120) had sRCC. When treated with immunotherapy-based regimens, sRCC and ccRCC patients had comparable PFS (HRadjusted: 1.13; 95% CI: 0.63–2.01; p = 0.68) and comparable OS (HRadjusted: 1.02; 95% CI: 0.99–1.05; p = 0.26). Conclusions This study suggests that the efficacy of HIF2αi may be limited in sRCC, possibly due to decreased dependency on HIF2α signaling. Our findings highlight the need for novel therapeutic strategies in sRCC.